Early Seedling Vigor and Morphology of Five Malaysian Indica Rice Cultivars under Water - Nulit, Rosimah; Akmal Zulhadi, Maizaitul Nurul; Yap, Chee Kong (Journal of Environmental Science and Engineering Technology, 2025)
This study evaluated the early seedling vigor and growth morphology of five Malaysian indica rice cultivars (MR263, MR219, MR220CL2, MR269, MR284) under simulated water deficit using polyethylene glycol (PEG 6000) treatments. Seeds were germinated on Petri dishes with four PEG solutions (0, –0.3, –0.9, –1.5 MPa) at 25°C. After 14 days, germination percentage, seedling vigor index, root length, and shoot (seedling) length were measured. Increasing osmotic stress significantly reduced germination speed and seedling growth for all cultivars, with the most severe stress (–1.50 MPa) causing drastic declines. Seedling vigor index decreased sharply as water potential decreased. Among cultivars, MR263 and MR219 maintained significantly higher vigor and longer roots/shoots under stress than the others. At –1.50 MPa, MR263 exhibited the highest vigor index ( 3.6), root length ( 5.8 cm) and shoot length ( 3.8 cm), whereas MR284 had the lowest ( 0.5, 2.7 cm, 0.3 cm, respectively). These results indicate genetic variation in drought tolerance at early stages. Our findings suggest MR263 and MR219 may be better suited for environments prone to water deficit, and highlight the importance of seed vigor and root development as selection criteria for drought resilience.